PENGEMBANGAN MODEL PEMBELAJARAN CASE METHOD DAN TEAM BASED PROJECT PADA MATA KULIAH PLH UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILL MAHASISWA DI ERA SOCIETY 5.0 - Putri, Agnestasia Ramadhani; Akhmad Nugraha; Izzah Muyassaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a learning model based on the Case Method and Team-Based Project in the Environmental Education (PLH) course to enhance students' higher order thinking skills in the Society 5.0 era. The model is developed through four learning modules, each consisting of three main phases: penetration, discussion, and project. In the penetration phase, students are introduced to fundamental concepts and relevant environmental cases through literature review and practical experiments. The discussion phase allows students to analyze cases in depth from various perspectives and design innovative solutions. In the project phase, students collaborate to develop and publish casebased projects, such as creating an environmental encyclopedia, organizing recycling campaigns, or producing digital educational content. The results indicate that this learning model increases student engagement in the learning process, strengthens analytical and problem-solving skills, and fosters innovation in developing environmental solutions. Moreover, students responded positively to this model as it provides a more interactive, contextual, and applicable learning experience aligned with the demands of the Society 5.0 era. Thus, the development of the Case Method and Team-Based Project model in the PLH course can serve as an innovative learning alternative to prepare students for the dynamic global challenges ahead.